Therapeutic interventions associated with improvements in the quality of life of patients with fibromyalgia: a systematic review (Research, Society and Development, 2022)
Fibromyalgia is a syndrome characterized by multifaceted symptoms that negatively impact the quality of life. With greater prevalence in women, the syndrome is manifested through widespread pain, fatigue, anxiety, and depression. While different interventions and guidelines for clinical management and diagnosis have been proposed, these are fraught with limiting factors due to the heterogeneity of associated symptoms, chronicity, and therapies with significative side effects. Based on the above, the objective of this study aims to evaluate the therapeutic interventions that improve the different domains of quality of life in patients with fibromyalgia. The research was conducted through systematic searches in the PUBMED, SCOPUS, LILACS and Web of Science databases between March 1, 2020, and May 08, 2021. Articles in Portuguese, English or Spanish were considered for analysis. To verify the risk of bias in each study, the levels of evidence were judged by two independent reviewers using the Cochrane collaboration tool. Articles in Portuguese, English or Spanish were considered for analysis. The scope of this review consisted of thirteen randomized clinical trials that met the pre-established inclusion criteria. The studies reviewed included 3,339 patients with a pre-established diagnosis of fibromyalgia, 92.2% of whom were female. Overall, fifteen interventions were observed that showed results for overall QOL and its physical and mental domains. The results showed high-quality evidence with positive findings for pain, physical functioning, anxiety, and depression with pharmacological and behavioral interventions. There is high-quality evidence supporting pregabalin for overall quality of life and the physical domain (pain and function), cognitive behavior therapy, and milnacipran for the physical domain of quality of life (pain and function), and moderate-quality evidence supporting cognitive behavioral therapy for the domain psychological (anxiety and depression).